Bridging Disciplines as a pathway to Finding New Solutions for Osteoarthritis a collaborative program presented at the 2019 Orthopaedic Research Society and the Osteoarthritis Research Society International. Issue 1 (March 2020) - Andriacchi, Thomas P.; Griffin, Timothy M.; Loeser, Richard F.; Chu, Constance R.; Roos, Ewa M.; Hawker, Gillian A.; Erhart-Hledik, Jennifer C.; Fischer, Arielle G.
Summary: Objective: To stimulate future research directions that seek solutions for osteoarthritis (OA) at the interface between diverse disciplines and address osteoarthritis (OA) as a serious disease with a complexity that has presented a barrier to finding safe effective solutions. Methods: Sessions were conducted at the 2019 meetings of the Orthopaedic Research Society (ORS) and Osteoarthritis Research Society International (OARSI) that included presentations and questions/comments submitted from leading OA researchers representing imaging, mechanics, biomarkers, phenotyping, clinical, epidemiology, inflammation and exercise. Results: Solutions for OA require a paradigm shift in research and clinical methods in which OA is contextualized as a complex whole-body/person disease. New OA definition(s)/phenotype(s) and OA markers/signals are needed to address the interplay between genetic and environmental factors of the disease as well as capture the mechanosensitivity of the disease. The term "Mechanokines" was proposed to highlight the importance of incorporating whole body mechanics as a marker of early OA. New interventions and apparent paradoxical observations/questions (e.g. exercise vs. load modification) were also discussed in the context of considering OA as a complex system. Conclusion: To advance new OA treatments that are safe and effective, OA should be considered as a "Whole Person" disease. This approach requires a concerted effort to bridge disciplines and include interactions across scales from the molecule to the whole body, including psychosocial aspects.